Some properties of d-codes. Issue 2 (3rd April 2021) - Cao, Chunhua; Liu, Haiyan; Yang, Di
Abstract : Since the union and the production of two d -codes may not be d -codes, in this paper, we aim to give some necessary and sufficient conditions for them.